Cephalosporin-Glycopeptide Combinations for Use against Clinical Methicillin-Resistant Staphylococcus aureus Isolates: Enhanced In vitro Antibacterial Activity - Tang, Hung-Jen; Lai, Chih-Cheng; Chen, Chi-Chung; Zhang, Chun-Cheng; Weng, Tzu-Chieh; Yu, Wen-Liang; Chen, Hung-Jui; Chiu, Yu-Hsin; Ko, Wen-Chien; Chuang, Yin-Ching (Frontiers in Microbiology, 2017)
Empirical combination of both a beta-lactam and a glycopeptide to cover potential staphylococcal pathogens may improve clinical outcome of the cases of Staphylococcus aureus bacteremia. We reported comparative in vitro studies of combination effects of different cephalosporins (i.e., cefazolin, cefmetazole, cefotaxime and cefepime) combined with glycopeptides for 34 randomly selected methicillin-resistant S. aureus (MRSA) isolates by three methods, including checkerboard, time-killing method and combination MIC measurement. Thirteen SCCmec type III isolates with a cefazolin MIC of ≥128 μg/ml were classified as the high-cefazolin MIC (HCM) group, whereas 13 SCCmec type IV and 8 SCCmec type V isolates as the low-cefazolin MIC (LCM) group. With the checkerboard method, for vancomycin-based combinations synergism was present in 30.8-69.2% and 13.6-66.7%, and teicoplanin-based combinations 38.5-84.6% and 0-47.6 % of the HCM and LCM isolates, respectively. No antagonism was noted. The in vitro inhibitory activity was evident even at a low concentration of 1/512x MIC of cephalosporin combined with sub-inhibitory concentrations (1/2x MIC) of a glycopeptide. With time-killing assays, synergism was noted at 1/2x or 1x susceptible breakpoint concentrations (SBCs) of a cephalosporin combined with 1/4 or 1/2 MIC of a glycopeptide. In the presence of 1/2 SBC of a cephalosporin, vancomycin or teicoplanin MICs decreased in average 2.0-6.6 or 1.6-5.5 fold, respectively. With the cephalosporin concentration at 8 μg/mL, the decline of glycopeptide MICs was most obvious in the presence of cefmetazole. In conclusion, cephalosporin-glycopeptide combinations at clinically achievable concentrations can exhibit in vitro synergistic antibacterial activity against clinical MRSA isolates. Such combinations require more clinical data to support their application for use in human MRSA infections.